The Village Gods of South India - Whitehead, Henry, (Brill | Manohar Publishers & Distributors, 2024)
Gramadevatas, or the village gods, are quite popular in the Indian subcontinent. During the ancient and medieval periods, village gods were venerated for religious, political, cultural, and social purposes for their blessings, well-being, divine powers, and good fortune. This book primarily focuses on the village gods prevalent in the southern states of India during the colonial period. It discusses the religion and ritual ceremonies in different parts of south India. Hinduism, and its particular forms, form a significant part of this book. A large part of the book covers the features concerning the religion, names of the deities, characteristics, functions, and the cult associated with each deity. Following this, the book covers the types of worship practiced in modern-day Karnataka, Andhra Pradesh, and Tamil Nadu. Lastly, the book covers folklore, the origins of various deities, and the impact on social systems based on social, moral, and religious aspects.